An exploratory assessment of pediatric patient and parent needs after implantable cardioverter defibrillator implant. Issue 3 (19th February 2020) - Schneider, Lauren M.; Wong, Jessie J.; Trela, Anthony; Hanisch, Debra; Shaw, Richard J.; Sears, Samuel F.; Motonaga, Kara S.; Ceresnak, Scott R.; Hood, Korey K.; Dubin, Anne M.
Abstract: Background: Placement of an implantable cardioverter defibrillator (ICD) is often accompanied by psychological adjustment issues in pediatric patients and their parents. Although anxiety, depression, and lowered quality of life have been seen in these patients, no studies have investigated patient or parent reported needs. This exploratory study describes the needs of pediatric ICD patients and parents and assesses whether patient factors of age, gender, depression, and anxiety are associated with specific needs. Methods: ICD patients ages 8‐21 years and their parents completed a needs analysis survey assessing various domains of functioning. Patients also completed self‐reported measures of depression and anxiety. Results: Thirty‐two patients (28% female) and their parents (72% mothers) completed the survey. Patients' most frequently endorsed needs involved educational issues: understanding their cardiac event/diagnosis (34%), medications (34%), and how the ICD would change their lifestyle (31%). Parents' most frequently endorsed needs involved family issues; almost half of parents (47%) were concerned about their children's frustration with their overprotectiveness and 28% were concerned with their child feeling depressed or anxious. Patients who reported feeling overprotected (12.1 ± 3.4 vs 17.4 ± 3.5 years; P  = .001) were significantly younger than those who did not. Experiencing peer issues was more frequently endorsed by females than males (33% of females vs 4% of males; P  = .026). Conclusions: ICD patients and parents endorsed markedly different needs. Patients focused on understanding their ICD, whereas parents were more focused on their children's emotional needs. Novel ways of educating patients about their device and clinic‐based screenings of emotional functioning may serve to meet these needs.